2017
DOI: 10.11648/j.ajns.20170604.13
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses' Knowledge, Practice, Obstacles and Helpful Measures Towards Palliative Care for Critically Ill Patients

Abstract: Palliative care (PC) is a specialized medical care for people with serious illnesses. It focuses on providing patients with relief from the symptoms, pain and stress of serious illness. The aim of the study is to assess critical care nurses' knowledge, practice, Obstacles and helpful measures toward palliative care for critically ill patients. The research design of this study was a descriptive design. It was conducted at Medical Intensive Care Unit (ICU) at Tanta University Hospital and oncology ICU at oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Knowledge was categorized as per the review of literature as poor <10 scores (<50% of total score), satisfactory 10–13 scores (50%–65% of total score), good 14–17 scores (66%–85% of total score), and excellent >17 scores (>85% of total score). [ 1 2 3 6 7 ]…”
Section: Ethodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge was categorized as per the review of literature as poor <10 scores (<50% of total score), satisfactory 10–13 scores (50%–65% of total score), good 14–17 scores (66%–85% of total score), and excellent >17 scores (>85% of total score). [ 1 2 3 6 7 ]…”
Section: Ethodsmentioning
confidence: 99%
“…The practice was categorized by the researcher as per the review of literature, as satisfactory >20 marks (>75% of total score) and poor ≤20 marks (≤75% of total score). [ 1 2 3 6 7 ]…”
Section: Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamal, Wolf [32] reported that inadequate preparedness of the nurses of both knowledge and practice sides was one of the most important obstacles was consistent with most of the reviewed articles [5,29,33], as they con rmed the importance of education on the practice level and provision of care. Moreover, this literature [30] has proved that inadequate timing is another important barrier to providing palliative care, as it prevents the nurses from providing the complete care practices that terminally ill patients require, and this was consistent with [34]. Others found the improper design of the ICU is another barrier that prevents nurses from providing the optimum palliative care [12].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, some studies found that clinical practice needed to be stronger [5,7]. Conversely, some studies have reported good and effective clinical practice in providing palliative care [30]. However, some studies have pointed out that practice is highly affected by the level of knowledge since the nurses who had good knowledge showed ideal and correct palliative care [5,18,31].…”
Section: Discussionmentioning
confidence: 99%